The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1113/expphysiol.1996.sp003920
|View full text |Cite
|
Sign up to set email alerts
|

Transport of sodium across the isolated bovine rumen epithelium: interaction with short‐chain fatty acids, chloride and bicarbonate

Abstract: De)pa t;nenit of. '1iitonix cind Phvsi(l/gy, The Rov!al eterifmar and Xgriiltura/l Universitv Bidonsvej 13, DK-1870 L' elderilsxberg C, ('opendhagen To wholl ciiCos pondcnce StldtnLl be adtdLtessed ,nt: The Dnish AoltitUtiLtUtrl Adtxisori C'onifCil, tUdkaersvej 1t. Skejhbv, DiK-8200, A l-blLls N. Dentn,r k.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
53
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 15 publications
11
53
0
Order By: Relevance
“…Chien & Stevens (1972) suggested that ruminal sodium and chloride transport are indirectly coupled due to the parallel existence of a Na¤-H¤ and Cl¦-HCOצ exchange. This hypothesis was confirmed in further studies by Martens & G abel (1988) and by Sehested et al (1996). The present study therefore was also designed to elucidate whether cAMP affects chloride transport.…”
supporting
confidence: 60%
“…Chien & Stevens (1972) suggested that ruminal sodium and chloride transport are indirectly coupled due to the parallel existence of a Na¤-H¤ and Cl¦-HCOצ exchange. This hypothesis was confirmed in further studies by Martens & G abel (1988) and by Sehested et al (1996). The present study therefore was also designed to elucidate whether cAMP affects chloride transport.…”
supporting
confidence: 60%
“…The initial G t and I sc values of the rumen preparations were consistent with previous studies (Sehested et al, 1996a, Aschenbach et al, 2000, Penner et al, 2010 and are representative of viable preparations. The EXT used in these experiments has previously been evaluated in vitro to determine if other compounds are present that could contribute to the observed effects of the EXT (Foote et al, 2012).…”
Section: Resultssupporting
confidence: 75%
“…the buffer contained HCO 3 − and did not contain Cl − or NO 3 − ) and bicarbonate-independent nitrate insensitive VFA flux (passive) by inducing maximal inhibition (i.e. addition of Cl − and NO 3 − and absence of HCO 3 − ) (Sehested et al, 1996a, Penner et al, 2009. Facilitated VFA flux was calculated as the difference between total and passive flux.…”
Section: Methodsmentioning
confidence: 99%
“…This context was used repeatedly to explain the stimulatory effects of Cl 2 on the electroneutral absorption of Na 1 , Mg 21 and Ca 21 across rumen epithelium Leonhard et al, 1991;Sehested et al, 1996;Leonhard-Marek et al, 2007a). Additional effects of Cl 2 on electrogenic cation absorption raised the hypothesis that apical Cl 2 channels might mediate a Cl 2 dependent change in membrane potential and thereby increase the electric driving force for cation uptake (Leonhard-Marek and Schrö der, 2002;Leonhard-Marek et al, 2006).…”
Section: Absorption and Secretion Of Chloridementioning
confidence: 99%